A Comparative Study of Floor Accelerations of Different Structural Systems with Lead- Rubber-Bearing (LRB) Isolators - Özuygur, Ali Ruzi (Canadian Science Publishing, 2020)
Seismic base isolation technique has been successfully used to protect structural as well as nonstructural components from the damaging effects of earthquakes by reducing floor accelerations and inter-story drifts for many decades. The level of floor acceleration is a key issue in the protection of acceleration-sensitive nonstructural components. The intensity of floor acceleration varies depending on the vibration characteristics of the structural system. Furthermore, the viscous damping devices sometimes are used to improve the performance of the superstructure as well as the base isolation system. The characteristics of the ground motions are also influential in the performance of the viscous damping devices. In this paper, the floor acceleration performance of seismically isolated buildings with different lateral load resisting systems such as moment resisting frame, dual system, moment resisting frame plus viscous wall dampers and dual system plus viscous wall dampers is investigated under near-fault and farfault earthquake ground motions. Moreover, the effectiveness of supplemental viscous damping devices equipped in parallel with lead-rubber-bearing isolators is studied. It is inferred from the study that the most effective way of reducing floor accelerations is to provide more rigidity to the superstructure. Utilizing supplemental viscous dampers along with lead-rubber-bearing isolators having about 20% of effective damping ratio is meaningless or harmful in relation to floor acceleration and base shear.
FSM Vakıf Üniversitesi, Mühendislik ve Fen Bilimleri Enstitüsü
Keywords: Seismic Base Isolation; Viscous Damping Devices; Near-Fault Ground Motions; Floor Acceleration; Viscous Wall Dampers